Implementation of Quality Assurance Protocols for an Advanced Linear Accelerator with Volumetric Modulated Arc Therapy Features Using Electronic Portal Imaging Device (EPID) - Bhatt, C. P.; Sharma, Kiran; Semwal, Manoj K. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*338.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0665);" role="presentation">To <span dir="ltr" style="left: calc(var(--scale-factor)*86.78px); top: calc(var(--scale-factor)*338.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.821111);" role="presentation">use <span dir="ltr" style="left: calc(var(--scale-factor)*103.58px); top: calc(var(--scale-factor)*338.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937465);" role="presentation">Electronic <span dir="ltr" style="left: calc(var(--scale-factor)*148.22px); top: calc(var(--scale-factor)*338.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949389);" role="presentation">Portal Imaging Device <span dir="ltr" style="left: calc(var(--scale-factor)*244.49px); top: calc(var(--scale-factor)*338.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968333);" role="presentation">(EPID), <span dir="ltr" style="left: calc(var(--scale-factor)*279.65px); top: calc(var(--scale-factor)*338.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93284);" role="presentation">an integral <span dir="ltr" style="left: calc(var(--scale-factor)*326.71px); top: calc(var(--scale-factor)*338.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888437);" role="presentation">feature <span dir="ltr" style="left: calc(var(--scale-factor)*357.91px); top: calc(var(--scale-factor)*338.45px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946939);" role="presentation">of a TrueBeam linear accelerator (linac) <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*351.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.876434);" role="presentation">system, <span dir="ltr" style="left: calc(var(--scale-factor)*108.14px); top: calc(var(--scale-factor)*351.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.990319);" role="presentation">for implementing <span dir="ltr" style="left: calc(var(--scale-factor)*187.01px); top: calc(var(--scale-factor)*351.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.939039);" role="presentation">dosimetry based <span dir="ltr" style="left: calc(var(--scale-factor)*261.65px); top: calc(var(--scale-factor)*351.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89441);" role="presentation">comprehensive <span dir="ltr" style="left: calc(var(--scale-factor)*328.03px); top: calc(var(--scale-factor)*351.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957925);" role="presentation">Quality Assurance <span dir="ltr" style="left: calc(var(--scale-factor)*411.43px); top: calc(var(--scale-factor)*351.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00121);" role="presentation">(QA) <span dir="ltr" style="left: calc(var(--scale-factor)*438.58px); top: calc(var(--scale-factor)*351.77px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.989271);" role="presentation">protocol needed for <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*364.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952069);" role="presentation">Volumetric Modulated Arc Therapy <span dir="ltr" style="left: calc(var(--scale-factor)*220.25px); top: calc(var(--scale-factor)*364.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01472);" role="presentation">(VMAT) modality. <span dir="ltr" style="left: calc(var(--scale-factor)*299.95px); top: calc(var(--scale-factor)*364.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.97221);" role="presentation">Varian <span dir="ltr" style="left: calc(var(--scale-factor)*330.07px); top: calc(var(--scale-factor)*364.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.8807);" role="presentation">makes <span dir="ltr" style="left: calc(var(--scale-factor)*358.27px); top: calc(var(--scale-factor)*364.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930535);" role="presentation">TrueBeam Version 2.0 <span dir="ltr" style="left: calc(var(--scale-factor)*453.10px); top: calc(var(--scale-factor)*364.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941531);" role="presentation">linac <span dir="ltr" style="left: calc(var(--scale-factor)*475.18px); top: calc(var(--scale-factor)*364.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.88393);" role="presentation">system <span dir="ltr" style="left: calc(var(--scale-factor)*505.90px); top: calc(var(--scale-factor)*364.97px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.998812);" role="presentation">with <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*378.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924593);" role="presentation">Intensity Modulated Radiotherapy (<span dir="ltr" style="left: calc(var(--scale-factor)*215.09px); top: calc(var(--scale-factor)*378.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.03599);" role="presentation">IMRT), <span dir="ltr" style="left: calc(var(--scale-factor)*248.69px); top: calc(var(--scale-factor)*378.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*265.61px); top: calc(var(--scale-factor)*378.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968804);" role="presentation">VMAT treatment <span dir="ltr" style="left: calc(var(--scale-factor)*337.87px); top: calc(var(--scale-factor)*378.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926253);" role="presentation">modalities w<span dir="ltr" style="left: calc(var(--scale-factor)*389.23px); top: calc(var(--scale-factor)*378.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.847983);" role="presentation">ere <span dir="ltr" style="left: calc(var(--scale-factor)*403.99px); top: calc(var(--scale-factor)*378.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.846139);" role="presentation">used <span dir="ltr" style="left: calc(var(--scale-factor)*424.90px); top: calc(var(--scale-factor)*378.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927194);" role="presentation">in the study. <span dir="ltr" style="left: calc(var(--scale-factor)*476.74px); top: calc(var(--scale-factor)*378.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927973);" role="presentation">The linac <span dir="ltr" style="left: calc(var(--scale-factor)*516.82px); top: calc(var(--scale-factor)*378.17px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923967);" role="presentation">is <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893217);" role="presentation">equipped <span dir="ltr" style="left: calc(var(--scale-factor)*113.42px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.992063);" role="presentation">with a <span dir="ltr" style="left: calc(var(--scale-factor)*144.62px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02299);" role="presentation">Multileaf Collimator (<span dir="ltr" style="left: calc(var(--scale-factor)*237.65px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02868);" role="presentation">MLC) <span dir="ltr" style="left: calc(var(--scale-factor)*267.29px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925415);" role="presentation">having <span dir="ltr" style="left: calc(var(--scale-factor)*298.99px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926334);" role="presentation">120 leaves <span dir="ltr" style="left: calc(var(--scale-factor)*348.19px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9791);" role="presentation">(millenium <span dir="ltr" style="left: calc(var(--scale-factor)*397.27px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02875);" role="presentation">MLC<span dir="ltr" style="left: calc(var(--scale-factor)*418.90px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.05937);" role="presentation">) a<span dir="ltr" style="left: calc(var(--scale-factor)*431.38px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904332);" role="presentation">nd <span dir="ltr" style="left: calc(var(--scale-factor)*446.02px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975591);" role="presentation">an EPID <span dir="ltr" style="left: calc(var(--scale-factor)*486.82px); top: calc(var(--scale-factor)*391.37px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886244);" role="presentation">(aS1000) <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*404.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925415);" role="presentation">having <span dir="ltr" style="left: calc(var(--scale-factor)*101.90px); top: calc(var(--scale-factor)*404.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906497);" role="presentation">megavoltage photon (<span dir="ltr" style="left: calc(var(--scale-factor)*189.53px); top: calc(var(--scale-factor)*404.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.07571);" role="presentation">MV) <span dir="ltr" style="left: calc(var(--scale-factor)*211.61px); top: calc(var(--scale-factor)*404.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895244);" role="presentation">detector system. The <span dir="ltr" style="left: calc(var(--scale-factor)*297.67px); top: calc(var(--scale-factor)*404.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958286);" role="presentation">EPID <span dir="ltr" style="left: calc(var(--scale-factor)*322.63px); top: calc(var(--scale-factor)*404.57px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91976);" role="presentation">has an active imaging area of 40 cm x 30 cm with <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*417.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917411);" role="presentation">1024 x 768-<span dir="ltr" style="left: calc(var(--scale-factor)*120.62px); top: calc(var(--scale-factor)*417.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971684);" role="presentation">pixel <span dir="ltr" style="left: calc(var(--scale-factor)*143.30px); top: calc(var(--scale-factor)*417.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957071);" role="presentation">matrix <span dir="ltr" style="left: calc(var(--scale-factor)*171.98px); top: calc(var(--scale-factor)*417.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945398);" role="presentation">with a pixel resolution of 0.39 mm. It is <span dir="ltr" style="left: calc(var(--scale-factor)*334.51px); top: calc(var(--scale-factor)*417.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911277);" role="presentation">capable of capturing 14-<span dir="ltr" style="left: calc(var(--scale-factor)*432.34px); top: calc(var(--scale-factor)*417.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903002);" role="presentation">bit images at 30frames <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878914);" role="presentation">per second. <span dir="ltr" style="left: calc(var(--scale-factor)*120.62px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941889);" role="presentation">We <span dir="ltr" style="left: calc(var(--scale-factor)*137.18px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916862);" role="presentation">carried out <span dir="ltr" style="left: calc(var(--scale-factor)*183.17px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968838);" role="presentation">the following <span dir="ltr" style="left: calc(var(--scale-factor)*239.57px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00777);" role="presentation">QA <span dir="ltr" style="left: calc(var(--scale-factor)*256.73px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.861422);" role="presentation">tests <span dir="ltr" style="left: calc(var(--scale-factor)*277.25px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.906574);" role="presentation">using the <span dir="ltr" style="left: calc(var(--scale-factor)*316.75px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.962685);" role="presentation">EPID: <span dir="ltr" style="left: calc(var(--scale-factor)*344.59px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.09886);" role="presentation">i) <span dir="ltr" style="left: calc(var(--scale-factor)*353.35px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974521);" role="presentation">Dynamic MLC (D<span dir="ltr" style="left: calc(var(--scale-factor)*427.66px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02875);" role="presentation">MLC) d<span dir="ltr" style="left: calc(var(--scale-factor)*460.42px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928524);" role="presentation">osimetry <span dir="ltr" style="left: calc(var(--scale-factor)*497.98px); top: calc(var(--scale-factor)*431.09px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960388);" role="presentation">test ii) <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*444.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00997);" role="presentation">DMLC po<span dir="ltr" style="left: calc(var(--scale-factor)*114.62px); top: calc(var(--scale-factor)*444.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930799);" role="presentation">sitional accuracy <span dir="ltr" style="left: calc(var(--scale-factor)*186.77px); top: calc(var(--scale-factor)*444.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.867004);" role="presentation">test (P<span dir="ltr" style="left: calc(var(--scale-factor)*213.41px); top: calc(var(--scale-factor)*444.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922042);" role="presentation">icket Fence test) <span dir="ltr" style="left: calc(var(--scale-factor)*284.81px); top: calc(var(--scale-factor)*444.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00921);" role="presentation">for fixed <span dir="ltr" style="left: calc(var(--scale-factor)*324.43px); top: calc(var(--scale-factor)*444.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959329);" role="presentation">and rotating gantry modes iii) <span dir="ltr" style="left: calc(var(--scale-factor)*451.54px); top: calc(var(--scale-factor)*444.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01718);" role="presentation">DMLC p<span dir="ltr" style="left: calc(var(--scale-factor)*488.98px); top: calc(var(--scale-factor)*444.29px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941757);" role="presentation">ositional <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892052);" role="presentation">accuracy <span dir="ltr" style="left: calc(var(--scale-factor)*112.22px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.861422);" role="presentation">test <span dir="ltr" style="left: calc(var(--scale-factor)*130.82px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941326);" role="presentation">during <span dir="ltr" style="left: calc(var(--scale-factor)*161.66px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936054);" role="presentation">rotation <span dir="ltr" style="left: calc(var(--scale-factor)*197.81px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.984008);" role="presentation">with intentional errors <span dir="ltr" style="left: calc(var(--scale-factor)*295.87px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.09867);" role="presentation">iv) d<span dir="ltr" style="left: calc(var(--scale-factor)*316.63px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.827933);" role="presentation">ose r<span dir="ltr" style="left: calc(var(--scale-factor)*338.11px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925884);" role="presentation">ate and g<span dir="ltr" style="left: calc(var(--scale-factor)*378.55px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929);" role="presentation">antry s<span dir="ltr" style="left: calc(var(--scale-factor)*407.59px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.852173);" role="presentation">peed <span dir="ltr" style="left: calc(var(--scale-factor)*431.38px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.840257);" role="presentation">tests <span dir="ltr" style="left: calc(var(--scale-factor)*453.82px); top: calc(var(--scale-factor)*457.51px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974942);" role="presentation">during RapidArc <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945746);" role="presentation">delivery and <span dir="ltr" style="left: calc(var(--scale-factor)*126.74px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.9924);" role="presentation">v) D<span dir="ltr" style="left: calc(var(--scale-factor)*146.06px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02868);" role="presentation">MLC l<span dir="ltr" style="left: calc(var(--scale-factor)*174.26px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888849);" role="presentation">eaf s<span dir="ltr" style="left: calc(var(--scale-factor)*194.33px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.852173);" role="presentation">peed <span dir="ltr" style="left: calc(var(--scale-factor)*217.13px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.861422);" role="presentation">test <span dir="ltr" style="left: calc(var(--scale-factor)*234.77px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972663);" role="presentation">during RapidArc delivery. <span dir="ltr" style="left: calc(var(--scale-factor)*346.39px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.14099);" role="presentation">All <span dir="ltr" style="left: calc(var(--scale-factor)*362.83px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*378.91px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.861422);" role="presentation">tests <span dir="ltr" style="left: calc(var(--scale-factor)*400.63px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.88805);" role="presentation">were <span dir="ltr" style="left: calc(var(--scale-factor)*423.70px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914011);" role="presentation">analys<span dir="ltr" style="left: calc(var(--scale-factor)*449.14px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.850184);" role="presentation">ed <span dir="ltr" style="left: calc(var(--scale-factor)*462.58px); top: calc(var(--scale-factor)*470.71px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99829);" role="presentation">with Microsoft <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*484.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930963);" role="presentation">Excel <span dir="ltr" style="left: calc(var(--scale-factor)*97.94px); top: calc(var(--scale-factor)*484.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929982);" role="presentation">application. <span dir="ltr" style="left: calc(var(--scale-factor)*148.10px); top: calc(var(--scale-factor)*484.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929386);" role="presentation">Deviations <span dir="ltr" style="left: calc(var(--scale-factor)*194.57px); top: calc(var(--scale-factor)*484.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94453);" role="presentation">of the EPID pixel values from known regions of interest during the various tests <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*497.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932267);" role="presentation">with respect to <span dir="ltr" style="left: calc(var(--scale-factor)*135.14px); top: calc(var(--scale-factor)*497.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926334);" role="presentation">open fields <span dir="ltr" style="left: calc(var(--scale-factor)*182.93px); top: calc(var(--scale-factor)*497.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895294);" role="presentation">were estimated <span dir="ltr" style="left: calc(var(--scale-factor)*246.65px); top: calc(var(--scale-factor)*497.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886127);" role="presentation">for accuracy assessment. <span dir="ltr" style="left: calc(var(--scale-factor)*349.99px); top: calc(var(--scale-factor)*497.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00909);" role="presentation">DMLC d<span dir="ltr" style="left: calc(var(--scale-factor)*386.95px); top: calc(var(--scale-factor)*497.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928524);" role="presentation">osimetry <span dir="ltr" style="left: calc(var(--scale-factor)*424.90px); top: calc(var(--scale-factor)*497.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.861422);" role="presentation">test <span dir="ltr" style="left: calc(var(--scale-factor)*441.94px); top: calc(var(--scale-factor)*497.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91999);" role="presentation">showed a maximum <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*510.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931049);" role="presentation">deviation <span dir="ltr" style="left: calc(var(--scale-factor)*113.42px); top: calc(var(--scale-factor)*510.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00562);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*126.02px); top: calc(var(--scale-factor)*510.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905081);" role="presentation">0.16 % <span dir="ltr" style="left: calc(var(--scale-factor)*160.70px); top: calc(var(--scale-factor)*510.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969638);" role="presentation">with respect to <span dir="ltr" style="left: calc(var(--scale-factor)*227.45px); top: calc(var(--scale-factor)*510.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958693);" role="presentation">reference condition at 0<span dir="ltr" style="left: calc(var(--scale-factor)*327.31px); top: calc(var(--scale-factor)*510.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968836);" role="presentation">º gantry. <span dir="ltr" style="left: calc(var(--scale-factor)*367.03px); top: calc(var(--scale-factor)*510.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973126);" role="presentation">The maximum p<span dir="ltr" style="left: calc(var(--scale-factor)*436.78px); top: calc(var(--scale-factor)*510.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961457);" role="presentation">ositional accuracy of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*523.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02106);" role="presentation">DMLC <span dir="ltr" style="left: calc(var(--scale-factor)*104.18px); top: calc(var(--scale-factor)*523.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933414);" role="presentation">was found to be <span dir="ltr" style="left: calc(var(--scale-factor)*173.18px); top: calc(var(--scale-factor)*523.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905081);" role="presentation">0.28 <span dir="ltr" style="left: calc(var(--scale-factor)*194.09px); top: calc(var(--scale-factor)*523.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936678);" role="presentation">mm <span dir="ltr" style="left: calc(var(--scale-factor)*212.93px); top: calc(var(--scale-factor)*523.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95401);" role="presentation">for fixed gantry and 0.26 <span dir="ltr" style="left: calc(var(--scale-factor)*319.03px); top: calc(var(--scale-factor)*523.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929449);" role="presentation">mm <span dir="ltr" style="left: calc(var(--scale-factor)*337.75px); top: calc(var(--scale-factor)*523.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(--scale-factor)*352.63px); top: calc(var(--scale-factor)*523.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932757);" role="presentation">rotating <span dir="ltr" style="left: calc(var(--scale-factor)*386.95px); top: calc(var(--scale-factor)*523.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92478);" role="presentation">gantry. <span dir="ltr" style="left: calc(var(--scale-factor)*418.30px); top: calc(var(--scale-factor)*523.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924318);" role="presentation">For varying dose rate and <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920823);" role="presentation">gantry <span dir="ltr" style="left: calc(var(--scale-factor)*100.22px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.837462);" role="presentation">speed, <span dir="ltr" style="left: calc(var(--scale-factor)*128.18px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893429);" role="presentation">the average of <span dir="ltr" style="left: calc(var(--scale-factor)*187.73px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*202.61px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.884922);" role="presentation">absolute <span dir="ltr" style="left: calc(var(--scale-factor)*238.73px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.901462);" role="presentation">value <span dir="ltr" style="left: calc(var(--scale-factor)*262.97px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*273.89px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1);" role="presentation">all <span dir="ltr" style="left: calc(var(--scale-factor)*286.61px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915165);" role="presentation">deviations <span dir="ltr" style="left: calc(var(--scale-factor)*330.31px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.07038);" role="presentation">Diff(x) <span dir="ltr" style="left: calc(var(--scale-factor)*361.51px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.868337);" role="presentation">was <span dir="ltr" style="left: calc(var(--scale-factor)*379.51px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905081);" role="presentation">0.43. <span dir="ltr" style="left: calc(var(--scale-factor)*402.31px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The <span dir="ltr" style="left: calc(var(--scale-factor)*420.58px); top: calc(var(--scale-factor)*536.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932908);" role="presentation">MLC leaf speed variation <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*550.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954721);" role="presentation">during RapidArc <span dir="ltr" style="left: calc(var(--scale-factor)*143.66px); top: calc(var(--scale-factor)*550.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92752);" role="presentation">resulted in <span dir="ltr" style="left: calc(var(--scale-factor)*189.65px); top: calc(var(--scale-factor)*550.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881658);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*205.25px); top: calc(var(--scale-factor)*550.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.859327);" role="presentation">average <span dir="ltr" style="left: calc(var(--scale-factor)*239.57px); top: calc(var(--scale-factor)*550.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.956048);" role="presentation">of the <span dir="ltr" style="left: calc(var(--scale-factor)*266.81px); top: calc(var(--scale-factor)*550.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.899873);" role="presentation">absolute <span dir="ltr" style="left: calc(var(--scale-factor)*303.55px); top: calc(var(--scale-factor)*550.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01728);" role="presentation">value of all Diff(x) <span dir="ltr" style="left: calc(var(--scale-factor)*385.15px); top: calc(var(--scale-factor)*550.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.957101);" role="presentation">of 0.20. <span dir="ltr" style="left: calc(var(--scale-factor)*420.34px); top: calc(var(--scale-factor)*550.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929646);" role="presentation">Similar results have <span dir="ltr" style="left: calc(var(--scale-factor)*504.58px); top: calc(var(--scale-factor)*550.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.852173);" role="presentation">been <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*563.35px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898537);" role="presentation">obtained <span dir="ltr" style="left: calc(var(--scale-factor)*110.54px); top: calc(var(--scale-factor)*563.35px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.992063);" role="presentation">with a <span dir="ltr" style="left: calc(var(--scale-factor)*140.42px); top: calc(var(--scale-factor)*563.35px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.07252);" role="presentation">film <span dir="ltr" style="left: calc(var(--scale-factor)*160.82px); top: calc(var(--scale-factor)*563.35px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928101);" role="presentation">based QA <span dir="ltr" style="left: calc(var(--scale-factor)*205.85px); top: calc(var(--scale-factor)*563.35px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909926);" role="presentation">tests. The <span dir="ltr" style="left: calc(var(--scale-factor)*249.65px); top: calc(var(--scale-factor)*563.35px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971156);" role="presentation">time taken in performing the above tests with EPID is far less as <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*576.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920658);" role="presentation">compared to the conventional methods. <span dir="ltr" style="left: calc(var(--scale-factor)*235.25px); top: calc(var(--scale-factor)*576.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93278);" role="presentation">EPID based QA tests are reliable and quick. We believe that protocols <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*589.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951806);" role="presentation">developed for performing QA tests with EPID can replace the conventi<span dir="ltr" style="left: calc(var(--scale-factor)*366.55px); top: calc(var(--scale-factor)*589.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955313);" role="presentation">onal methods of QA. <span dir="ltr" style="left: calc(var(--scale-factor)*457.06px); top: calc(var(--scale-factor)*589.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.912047);" role="presentation">EPID based <span dir="ltr" style="left: calc(var(--scale-factor)*509.14px); top: calc(var(--scale-factor)*589.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00008);" role="presentation">QA <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*602.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93051);" role="presentation">will result in considerable time saving and <span dir="ltr" style="left: calc(var(--scale-factor)*245.57px); top: calc(var(--scale-factor)*602.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934422);" role="presentation">thus helpful <span dir="ltr" style="left: calc(var(--scale-factor)*295.99px); top: calc(var(--scale-factor)*602.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917149);" role="presentation">in increasing the patient <span dir="ltr" style="left: calc(var(--scale-factor)*395.35px); top: calc(var(--scale-factor)*602.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920736);" role="presentation">throughput <span dir="ltr" style="left: calc(var(--scale-factor)*442.06px); top: calc(var(--scale-factor)*602.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967269);" role="presentation">in a clinic. Also, <span dir="ltr" style="left: calc(var(--scale-factor)*511.30px); top: calc(var(--scale-factor)*602.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.873747);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*616.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.969622);" role="presentation">quicker and automated QA procedure <span dir="ltr" style="left: calc(var(--scale-factor)*238.49px); top: calc(var(--scale-factor)*616.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974593);" role="presentation">based on EPID <span dir="ltr" style="left: calc(var(--scale-factor)*309.07px); top: calc(var(--scale-factor)*616.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878036);" role="presentation">lends <span dir="ltr" style="left: calc(var(--scale-factor)*335.11px); top: calc(var(--scale-factor)*616.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.98141);" role="presentation">itself <span dir="ltr" style="left: calc(var(--scale-factor)*360.31px); top: calc(var(--scale-factor)*616.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975277);" role="presentation">to better compliance and <span dir="ltr" style="left: calc(var(--scale-factor)*472.18px); top: calc(var(--scale-factor)*616.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923354);" role="presentation">hence better <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*629.50px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929539);" role="presentation">treatment quality